Karakterisasi Struktur Coating Fe-25Al Yang Difabrikasi Dengan Metode Paduan Mekanik [Structure Characterization of Fe-25Al Coating Fabricated by Mechanical Alloying Method] - Nisa, Khoirun; Aryanto, Didik; Sudiro, Toto; Sebayang, Perdamean; Aji, Mahardika P (Metalurgi, 2016)
Fe-25Al coating has been prepared on low carbon steel substrate by using a mechanical alloying technique. Structure of Fe-25Al coating before and after heat treatment at 600, 700, and 800 °C was studied by using XRD (x-ray diffraction) characterization. SEM (scanning electron microscopy) and EDX (energy disperse xray) were used to identified the morphology of cross-section of Fe-25Al coating after mechanical alloying process. The result of SEM, EDX and XRD showed that the Fe-25Al deposited uniformly on low carbon steel. The Fe-25Al coating formation has a solid solution Fe(Al) phase. Heat treatment caused the changing in the phase of Fe-25Al coating, where the Fe3Al phase with orientation of (110), (200) and (211) plane was formed. The optimum of diffusion process was occurs at temperature of 600C which was indicated by the increasing in the crystalline size and followed by the decreasing in the dislocation density and lattice strain. Increasing temperature on the heat treatment caused the changing in the structure parameter, such as lattice parameter, crystalline size, lattice strain and dislocation density. In this work, heat treatment on the Fe-25Al coating influenced the changing in crystal defect such as grain boundaries, vacancy and dislocation. It affected thechanges of lattice strain and crystalline size of Fe-25Al coating.AbstrakCoating Fe-25Al telah dipreparasi di atas substrat baja karbon rendah dengan menggunakan metode paduan mekanik. Struktur dari coating Fe-25Al sebelum dan setelah diberi perlakuan panas pada 600°C, 700°C, and 800°C dipelajari dengan menggunakan karakterisasi X-ray diffraction (XRD). Scanning electron microscopy (SEM) dan energy disperse X-ray (EDX) digunakan untuk mengetahui morfologi dari penampang lintang coating Fe-25Al setelah proses paduan mekanik. Hasil dari SEM, EDX dan XRD menunjukkan bahwa Fe-25Al telah terdeposisi seragam pada substrat baja karbon rendah. Coating Fe-25Al yang terbentuk memiliki fasa solid solution Fe(Al). Perlakuan panas menyebabkan perubahan fasa pada coating Fe-25Al, dimana terbentuk fasa Fe3Al dengan orientasi bidang (110), (200) dan (211). Proses difusi optimum terjadi pada suhu 600°C yang ditunjukkan dengan peningkatan ukuran butir, diikuti dengan berkurangnya densitas dislokasi dan regangan kisi. Meningkatnya suhu pada perlakuan panas menyebabkan perubahan parameter struktur seperti parameter kisi, ukuran kristal, regangan kisi dan kerapatan dislokasi. Dalam pekerjaan ini, perlakuan panas pada coating Fe-25Al mempengaruhi perubahan cacat kristal seperti batas butir, kekosongan dan dislokasi. Hal tersebut berakibat pada perubahan regangan kisi dan ukuran kristal dari coating Fe-25Al.